2017
DOI: 10.1155/2017/7218918
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Disinfection by Pulse Irrigation with Povidone-Iodine Solution in Spine Surgery

Abstract: Background Deep wound infection in spine surgery is a debilitating complication for patients and increases costs. The objective of this prospective study was to evaluate the efficacy of wound pulse irrigation with a dilute povidone-iodine solution in the prevention of surgical site infection. Methods 50 patients undergoing spinal surgery were randomly divided into two groups (A and B) of 25 patients each. In group A, wounds were irrigated with dilute (3%) povidone-iodine solution through a low-pressure pulsati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…Fourteen studies provided a clear definition of SSI. In 5 studies, 32,4446,48 this was the (deep) SSI definition used by the Centers for Disease Control and Prevention. 50 Three studies defined SSI as a combination of clinical symptoms, elevated serum inflammation markers (erythrocyte sedimentation rate, C-reactive protein, white blood cell count), and bacterial culture results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fourteen studies provided a clear definition of SSI. In 5 studies, 32,4446,48 this was the (deep) SSI definition used by the Centers for Disease Control and Prevention. 50 Three studies defined SSI as a combination of clinical symptoms, elevated serum inflammation markers (erythrocyte sedimentation rate, C-reactive protein, white blood cell count), and bacterial culture results.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 20 included studies, 2 were RCTs 30,31 and 18 were observational cohort studies (Table 1). 32 49 Eight studies investigated many different types of spinal surgery. 30,38 41,43,46,47 Five studies investigated deformity surgery, in either adults, 42 children, 45,48,49 or both.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many infection control measures, recommended for every surgery with sufficient evidence, have been tried, yet other measures that have also shown effectiveness are not commonly used because their application has been limited to spinal surgery cases only, with low evidence levels. Several studies have demonstrated infection prevention interventions to reduce infection rates in patients undergoing spinal surgeries, including irrigation with povidoneiodine solution, 6,7 prophylactic vancomycin administration, 8,9 and intrawound vancomycin powder. 10,11 However, applying complex and expensive infection prevention interventions in every patient undergoing surgery may result in poor allocation of limited human, temporal, and medical resources.…”
mentioning
confidence: 99%